Tube Dilution Antimicrobial Susceptibility Testing: Efficacy of a Microtechnique Applicable to Diagnostic Laboratories - Chitwood, Lawrence A. (1969)
A microtechnique for determining antibiotic susceptibilities by the serial dilution method was evaluated in a clinical diagnostic microbiology laboratory. As compared with the standard tube method, an agreement of 94% was achieved for determining minimal inhibitory concentration with ± one tube dilution as the criterion of comparison. The experience with this system suggests that it could easily be incorporated into diagnostic laboratories as a routine procedure.